Раскопки поселения поздней бронзы возле г. Зимогорье на р. Лугань - Пробейголова, А.С.; Красильников, К.И. (Археологічні дослідження в Україні, 2010)
In 2009 season, the expedition of Luhansk Department of the Eastern Ukraine Branch of the IA NASU conducted rescue archaeological research at the Late Bronze Age settlement near Zymohirya in the Luhansk River region. The remains of two stone buildings exposed to the intensive devastation by the erosion were studied. The material found in the filling and on the floor of the buildings belongs to the late stage of Zrubna cultural and historical community.